KEBIJAKAN PEMERINTAH DAERAH TERHADAP PENANGANAN STANTING DI KABUPATEN HALMAHERA TIMUR - Mohbir Umasugi; Ridho Harta; Muhammad Darsan Hi Adam (Halu Oleo University, 2024)
This study is intended to explain how the stunting prevention policy for East Halmahera Regency with the highest stunting prevalence in North Maluku Province. This study also intends to find out how the policies are initiated by the local government and the relevance of their implementation in the community. This study uses a qualitative method with a descriptive approach. Data sources are obtained through interviews with relevant stakeholders. Data are processed through data collection, data analysis, and drawing conclusions and policy suggestions or recommendations. The results of the study show that the Central Halmahera Regency Local Government Policy in handling stunting is not optimal, as seen from the high stunting rate which places this district in first place in North Maluku in 2022. Interventions through anthropometric measurements are effective in increasing awareness of mothers and health cadres about the importance of nutritional status, while training in making PMT provides practical knowledge about healthy toddler menus. In the future, further counselling is needed on exclusive breastfeeding and complete basic immunization to support efforts to prevent stunting sustainably.